Ringkasan dan Ulasan NOVEL INDONESIA MODERN - Mahayana, Maman S., 1957-; Dian, Achmad, 1955-; Sofyan, Oyon, 1955-; Nusantara, A. Ariobimo (Jakarta : Gramedia Widiasarana Indonesia, 2007)
Summary and criticism of modern Indonesian novels
Includes bibliographical references page: 383-386
Keywords: Indonesian fiction -- 20th century -- History and criticism; Criticism, interpretation, etc